Jupiter's North Equatorial Belt expansion and thermal wave activity ahead of Juno's arrival. Issue 14 (31st July 2017) - Fletcher, L. N.; Orton, G. S.; Sinclair, J. A.; Donnelly, P.; Melin, H.; Rogers, J. H.; Greathouse, T. K.; Kasaba, Y.; Fujiyoshi, T.; Sato, T. M.; Fernandes, J.; Irwin, P. G. J.; et al.
Abstract: The dark colors of Jupiter's North Equatorial Belt (NEB, 7–17°N) appeared to expand northward into the neighboring zone in 2015, consistent with a 3–5 year cycle. Inversions of thermal‐IR imaging from the Very Large Telescope revealed a moderate warming and reduction of aerosol opacity at the cloud tops at 17–20°N, suggesting subsidence and drying in the expanded sector. Two new thermal waves were identified during this period: (i) an upper tropospheric thermal wave (wave number 16–17, amplitude 2.5 K at 170 mbar) in the mid‐NEB that was anticorrelated with haze reflectivity; and (ii) a stratospheric wave (wave number 13–14, amplitude 7.3 K at 5 mbar) at 20–30°N. Both were quasi‐stationary, confined to regions of eastward zonal flow, and are morphologically similar to waves observed during previous expansion events. Plain Language Summary: A campaign of Earth‐based support imaging for NASA's Juno mission identified several interesting atmospheric phenomena at work in Jupiter's northern hemisphere. The prominent dark brown belt north of the equator expanded northward, potentially spawning wave activity throughout the troposphere and stratosphere. Unlike previous cyclic events on Jupiter (these expansions occur once every 3–5 years), the 2015/2016 expansion stalled and did not reach completion, but the waves were evident throughout 2016 ahead of Juno's arrival in orbit around Jupiter. Such Earth‐based supporting observations help set the environmental context for Juno's close‐up observations of the giant planet. Key Points: Jupiter's North Equatorial Belt expanded northward in 2015/2016 as part of its 3–5 year activity cycle The expanded sector warmed, removing light‐colored aerosols to reveal darker colors at depth Significant thermal waves were identified in the troposphere and stratosphere at the time of the expansion